Galaxies: a perspective from its origins - Lambas, Diego Garcia (Cadernos de Astronomia, 2024)
This short article aims at setting relevant properties of galaxies in the light of recent studies. By putting particular emphasis on their formation and evolution, key issues such as the importance of accretion, dark matter, and feedback astrophysical process are briefly discussed.